In-situ testing for characterizing the landslide deposit in Jiuzhaigou cultural heritage site after the 2017 earthquake - Pei, Xiangjun; Jiang, Tao; Cui, Shenghua; Guo, Bin; Liang, Jing (Frontiers in Earth Science, 2023)
The Jiuzhaigou cultural heritage site in China is famous for its stunning calcium lakes, waterfalls, and a large-scale karst water system considered the "king of water scenery". The 2017 Jiuzhaigou earthquake caused numerous landslide masses in the Jiuzhaigou cultural heritage site, leading to frequent surface mass movement and affecting the hydrological landscape. This was the first time a strong earthquake hit the heritage site in China, making it an important area for ecological geological environment protection and restoration research. To understand the influence of slope runoff erosion on the activation of landslide accumulations, this study examined remote sensing images from 2017 to 2020 to investigate the geological disaster, while field scour tests were conducted to study the rainfall seepage, mass erosion, and migration. Results indicated that the steep-sloped landslide deposits in the heritage site contain a high content of fine grains and good permeability. The erosion on the landslide deposit slope surface is characterized by surface erosion, down-cutting, headward erosion, and lateral erosion. The downward spreading of the wetting front leads to an increase in volumetric water content and pore water pressure in the slope, while the matric suction continuously decreases after a narrow range of fluctuation.After the water pressure reaches its peak, the deposit reaches a stable state. The study suggested that the increase in water content, sharp increase in pore water pressure, rapid decrease in matric suction, and strong runoff erosion are the reasons for the widespread initiation of these landslide deposits. It was proposed that monitoring rainfall in the study area is necessary due to the concentration of heavy rainfall in a short amount of time, which is an important cause of landslide deposit instability. It highlights the importance of rainfall monitoring for landslide deposits due to the high rainfall concentrated in a short time is a significant cause of instability. The results of this study are of significance for the prediction of long-term effects and ecological governance of post-earthquake debris flow in cultural heritage site.